2020
DOI: 10.1128/aac.01865-19
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Different Antistaphylococcal Therapies, Alone or Combined, in a Rat Model of Methicillin-Resistant Staphylococcus epidermidis Osteitis without Implant

Abstract: We developed a rat model of methicillin-resistant Staphylococcus epidermidis (MRSE) osteitis without implant to compare the efficacy of vancomycin, linezolid, daptomycin, ceftaroline, and rifampin either alone or in association with rifampin. A clinical strain of MRSE was inoculated into the proximal tibia. Following a 1-week infection period, rats received either no treatment or 3, 7, or 14 days of human-equivalent antibiotic regimen. Quantitative bone cultures were performed throughout the 14-day period. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The CRIOGO centers have solid experience of linezolid use in the treatment of device infections. Animal studies demonstrated its efficacy in the treatment of BJIs due to Gram-positive cocci ( 26 , 27 ), and clinical data showed satisfactory efficacy in the treatment of device infections ( 28 ). The incidence of LR-MDRSE carriage appears to be directly related to linezolid consumption in health care facilities ( 14 19 ), and reducing consumption of oxazolidinones could help limit this incidence ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CRIOGO centers have solid experience of linezolid use in the treatment of device infections. Animal studies demonstrated its efficacy in the treatment of BJIs due to Gram-positive cocci ( 26 , 27 ), and clinical data showed satisfactory efficacy in the treatment of device infections ( 28 ). The incidence of LR-MDRSE carriage appears to be directly related to linezolid consumption in health care facilities ( 14 19 ), and reducing consumption of oxazolidinones could help limit this incidence ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…All administrations were given intraperitoneally, treatment duration was seven days. Dosing frequency and actual dosage was based on previous studies on all drugs and reflect common practice when using the selected antibiotics in rat models of S. aureus infection [ [22] , [23] , [24] , [25] ]. Rats were sedated followed by removal of the graft and euthanized by cervical dislocation 36 h after the final administration of treatment to ensure antibiotics washout before CFU enumeration.…”
Section: Methodsmentioning
confidence: 99%
“…3 . The tibia osteomyelitis rat model was established as previously described by Albac et al ( 22 ). Animals were anaesthetized by intraperitoneal administration of ketamine (90 mg/kg of body weight, Virbac) and xylazine (10 mg/kg of body weight, Bayer).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were randomly assigned to one of the four study arms: no treatment (0.9% saline serum), ceftaroline alone (20 mg/kg/12 h), rifampin alone (25 mg/kg/12 h), ceftaroline (20 mg/kg/12 h), and rifampin (25 mg/kg/12 h). Ceftaroline dose used in our published rat osteomyelitis model was administered, and rifampin dose was selected on the basis of data published in a rat model of MRSA osteomyelitis ( 22 , 41 )).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation